Analysis of Formation of Optimal Portfolio Single Index Model (Study of Cigarette Sub-Sector Manufacturing Companies Period 2020-2021) - Juliana, Nita; Djuanda, Dr. Gustian (Westscience Press, 2023)
Investors and the general public are becoming increasingly familiar with stock investing. This study aims to establish the appropriate proportion for stock and fund portfolios. Secondary data is the data's source. Cigarette manufacturing businesses served as the research population from January 2020 to December 2021. This study employs sampled four business companies single index model methodologyfirmsia (GGRM), which has a proportion of 33.81%, and PT. Handjaya Mandala Tobacco Tbk, which has an investment value of 66.19%, are the two shares that will be included in the optimal portfolio.